2007
DOI: 10.2174/092986707780059670
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through RAS-RAF-MEK-ERK: from Basics to Bedside

Abstract: Aberrant signaling caused by mutations in the RAS-RAF-MEK-ERK pathway and its upstream activators critically contributes to human tumor development. Strategies, which aim at inhibiting hyperactive signaling molecules, appear conceptually straight forward, but their translation into clinical practice has been hampered by many setbacks. Understanding structure, function and regulation of this intracellular pathway as well as its crosstalk with other signaling activities in the cell will be essential to ensure re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 139 publications
(224 reference statements)
1
85
0
1
Order By: Relevance
“…5,33 In this study, we have identified loss of the C-RAF --MEK inhibitor RKIP as an additional frequent molecular event affecting this crucial signaling pathway in AML. So far, several lines of evidence have established RKIP as a metastasis suppressor in solid neoplasms.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…5,33 In this study, we have identified loss of the C-RAF --MEK inhibitor RKIP as an additional frequent molecular event affecting this crucial signaling pathway in AML. So far, several lines of evidence have established RKIP as a metastasis suppressor in solid neoplasms.…”
Section: Discussionmentioning
confidence: 89%
“…Transmission of signals from the cell surface to intracellular effectors within this pathway is mediated by RAS-induced activation of a three-tiered kinase cascade comprising RAF, MEK and MAPK/ERK. 5,6 Oncogenic mutations affecting this pathway are frequently observed in human cancers with NRAS or KRAS mutations occurring in about 20% of AML patients. 5 Constitutive RAS-MAPK/ERK signaling is also initiated by somatic mutations in genes encoding the upstream FLT3 and c-Kit receptor tyrosine kinases in an additional 25 --40% of AML cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their activation is a complex process involving interactions with proteins and lipids as well as phosphorylation and requires the assembly of signalosomes, which, along with the core components of the signaling cascade, contain accessory molecules required for modulation, compartmentalization, and specificity (1)(2)(3). RAF kinases are upstream of a three-tiered mitogen-activated protein kinase (MAPK) cascade comprising the dual-specificity Ser/Thr MAPK kinases (MAP2K) MEK1/2 and their substrates ERK1/2, which are required for most reported RAF effects (4,5). Several proteins have been described, which may be important for RAF activation and signaling under specific conditions at distinct cellular sites.…”
Section: Introductionmentioning
confidence: 99%
“…Ras receives extracellular signals from membrane receptors and recruits various effectors to the plasma membrane [11]. Raf, an important Ras effector, then phosphorylates Mek, which in turn phosphorylates the Erk/MAPK kinases that relay information to multiple cytoplasmic and nuclear effector targets [12].…”
Section: Introductionmentioning
confidence: 99%